Plastic relief sculpture: Improving Nigerian students’ performance in practical biology - Michael Olubunmi Odewumi; David Akinjide Akintola; Isyaka Bello (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Among the factors identified to be responsible for the poor performance of senior high school students in biology is inappropriate instructional media. This study investigated the effects of plastic relief sculpture on senior high school students’ performance in biology practical activity in Ogbomoso, South Local Government Area of Oyo State, Nigeria. Moreover, it also observed gender as the moderating effect in this study. The population of this quasi-experimental study was the all senior high school biology students in Oyo State. Two intact classes of 120 biology students were randomly sampled for the study. Two instruments were used in this study i.e. Students’ Biology Practical Test and Biology Practical Lesson Notes. The findings of this study revealed that there was significant difference existed between the performance of students in the experimental and control group (F (8, 51) = 1.89, p < 0.05). Meanwhile, female students performed insignificantly different compared with male students (t (118) = 7.16, p = 0.12). Therefore, the study concluded that plastic instructional relief sculpture is effective in improving students’ performance in biology. Thus, it is recommended that teachers should adopt plastic relief sculpture as the innovative instructional resource in teaching biology.